Improving Understanding of Aqidah Material through The Fitrah Quiz Application at PPMI Assalam Sukoharjo - Hamidah, Anisa; Nurrohim, Ahmad; Nirwana, Andri (Universitas Muhammadiyah Surakarta, 2023)
Purpose: The app is designed to provide an interactive and engaging learning experience for students, with the goal of improving their understanding of aqidah material. Through the use of this application, students can study independently and at the desired time. Methodology: This study uses classroom action research carried out in two cycles with 22 grade VIII students as research subjects. Result: The result of this study is that the Fitrah Kuiz application helps improve student understanding, starting from students becoming more understanding of the material, interactive, and active. Application/originality/value: This research is expected to help provide new methods or ways for teachers to improve their understanding of the aqidah material for students in grade VIII PPMI ASSALAM Sukoharjo. It is also hoped that the method can be practiced for other schools in various regions.